Elevated Levels of Macrophage Migration Inhibitory Factor in Women with Metabolic Syndrome - Kim, H.- R.; Lee, S.- A.; Kim, H.J.; Kong, M. H.; Kim, Y. R.; Kang, S. H.; Lee, K.- H.; Leng, L.; Lee, B.- J.; Park, C. G.; Kook, Y.- H.; Kim, B.- J.; Bucala, R. (Hormone and Metabolic Research, 2011)
Metabolic syndrome is a complex clinical disorder characterized by obesity, a disturbance of glucose metabolism, dyslipidemia, and hypertension, leading to increased cardiovascular risk. Macrophage migration inhibitory factor (MIF) is a proinflammatory cytokine produced both by innate immune cells and by adipocytes, and it plays an important role in inflammatory and cardiovascular diseases. The goal of this study was to evaluate the expression of circulating MIF in patients with metabolic syndrome. A study was conducted involving 172 persons who attended the Jeju National University Hospital Health Promotion Center. Among the 172 subjects, 88 patients with metabolic syndrome and 84 healthy control subjects were included. Serum MIF levels were considerably higher in patients with metabolic syndrome than in healthy subjects (mean±SEM, 1413.0-pg/ml±102.6 vs. 1077.0-pg/ml±-91.3, p=0.016). Among the metabolic syndrome patients, MIF levels were significantly increased in women (1403.0-pg/ml±114.2 vs. 921.3pg/ml±117.3, p=0.005), but not in men. Even after further linear regression adjustment for age and body mass index, the expression of MIF for women with metabolic syndrome was still clearly elevated when compared to healthy subjects (p=0.011). Circulating MIF concentrations showed a gender disparity between healthy and metabolic syndrome subjects. An elevation of systemic MIF in women with metabolic syndrome may contribute to pathogenesis of metabolic syndrome or to the development of metabolic syndrome-related diseases, such as atherosclerosis and type 2 diabetes mellitus.
Keywords: MIF; metabolic syndrome; cytokines; human